A new species of Mimosa (Leguminosae) from Brazil - Jordão, Lucas Sá Barreto; Morim, Marli Pires; Baumgratz, José Fernando Andrade (Phytotaxa, 2014)
A new species of Mimosa is described from the Atlantic Rainforest and ecotone with the Cerrado of southeastern Brazil, in the states of Minas Gerais, Rio de Janeiro and São Paulo: M. porrecta L. Jordão, M.P. Morim & Baumgratz (Leguminosae). Related to M. sensitiva, it shares morphological affinities with this species but differs in having porrect-stellate trichomes, a new type of trichome for the genus, on the stems, and the dendritic trichomes in the fruits. The conservation status was assessed, according to IUCN criteria, as Least Concern.